Profil Kemandirian Belajar Mahasiswa Pendidikan Matematika di Masa Pandemi Covid-19 - Hajerina Hajerina; Indah Suciati; Dewi Sri Wahyuni (SJME (Supremum Journal of Mathematics Education), 2022)
To describe the profile of the learning independence of Mathematics Education students at Alkhairaat University Palu during the Covid-19 Pandemic is the purpose of this study. Descriptive research with a qualitative approach is the method used in the research. The learning independence scale is given to students of the Mathematics Education Study Program at Alkhairaat University Palu in the third semester of the 2020-2021 academic year as a research instrument. Furthermore, 3 students who have high, medium, and low abilities were selected as subjects in the study. Data were collected through questionnaires and interviews. The stages of data analysis carried out refer to the Miles & Huberman model, namely data reduction, data presentation, and drawing conclusions and verification. The findings describe nine indicators of student learning independence at each level of academic ability (high, medium, and low). From these findings, it was found that 1) the learning independence of mathematics education students during the Covid-19 pandemic was different for each level of academic ability, 2) students with high academic abilities met all indicators of learning independence very well, (3) students with moderate academic ability meets most indicators of learning independence very well, and (4) students with low academic ability meet several indicators of learning independence very well.